Analyzing morphologic dynamics in poor urban areas through earth observation: The case of the Purulia, West Bengal, India - Samyakami Kaibarta; Edris Alam; Khawla Saeed Al Hattawi; Somnath Mandal; Pintu Mandal; Subhasis Bhattacharya; Suman Paul (Social Sciences and Humanities Open)
The slum is the shadow of urbanization, representing a lack of essential services, substandard housing, a congested, unhygienic environment, and poverty. Slum morphology depicts the structural arrangement of a slum area, including the road network, building arrangement, cultural artefacts, etc. Slums in megacities like Mumbai, Kolkata, Delhi, etc, have developed naturally or as a result of urbanization. However, apart from megacities, only some areas or few towns, particularly those serving as headquarters of the districts, have a considerable impact on their hinterlands. Purulia town, as the district headquarters, acts as a pull factor, which stimulates the growth of the slum area of its hinterland. Hence, Purulia was selected as a study area. The focus of this study is the morphological dynamicity of slums in Purulia, therefore the temporal analysis is necessary. Additionally, it aims to apprehend the trend and pattern of slum expansion over time in Purulia municipality. This study uses satellite images and secondary data sources (DPR for BLC under Housing for All in slums, Purulia Municipality, 2015–2016) to analyze the dynamicity of slum morphology. Structural appurtenance of the area was measured using spatial variables including, the number of buildings, and the size of the building, building orientation, building density, and heterogeneity. This spatiotemporal analysis depicts inter and intra-slum variation and detects distinct but predominantly high morphological transformation throughout the eight slums. A compact building structure with a particular heterogeneous pattern is shown in many slums. However, some slums remain almost static, experiencing minimal but haphazard morphological transformation. Street patterns, including lane-to-lane, road-to-lane, house-to-house connections, water bodies' presence, and urban planning regulations such as zoning restrictions on high-rise construction etc., influence the slum growth and transform the morphological dynamicity. Apart from structural morphology, it also reflects solid social bonding and cohesion among slum communities. Overall, this research emphasizes the intricate interplay of factors driving morphological dynamicity within the slum area, encompassing socio-economic conditions, population dynamics, neighborhood characteristics, and governmental policies. It emphasizes the need for extensive policy planning for slum upgrading and creating strategies for dwellers to secure land ownership. It also implements a systematic approach to constant monitoring of poor slum areas to capture morphological dynamicity using very high-resolution Earth observation data. This may provide a better understanding of morphological transformations over time and guide policy-making decisions.